RETURN AS KAMPUNG: A DEVELOPMENT THINKING PERSPECTIVE OF KAMPUNG SUSUN AKUARIUM REDEVELOPMENT - Delfirman Delfirman; Muhammad Nabiel Rahardjo; Febrian Giovani; Sonny Yuliar (Diponegoro University, 2024)
The Development of Kampung Susun Akuarium has caused many changes. The kampung community had experienced a downturn because they lost their homes, livelihoods and social environment, but they chose to rise again. This research uses a development thinking framework in analyzing the way of views or values of the community, ideas of progress, agents involved, resources, and patterns of change that occur in the kampung community. This framework makes it possible to see community change in various aspects and provides an alternative perspective on development. The qualitative method was carried out with observations and interviews with the community and local leaders, coupled with a review of related literature. As a result, we found that the values as a unified Kampung community continue to be maintained amidst the change. Then, independence and increased capability become the criteria of progress for the community that is being strived for. This is done by actors or institutions that mainly come from the grassroots, namely Koperasi and non-governmental organizations, through community empowerment efforts in improving livelihoods. The local government itself tends to be constrained by internal political dynamics, resulting in a lack of sustainability of the Development program. Finally, the revival of kampung communities is pursued primarily by the communities themselves.